Laparoscopy for Abdominopelvic Emergencies at the Auxerre Hospital: Patients’ Epidemiological Profile, Diagnostic and Therapeutic Contribution - ATTOLOU, SÈTONDJI GILLES ROGER; MEHINTO, KUASSI DELPHIN (My University, 2022)
This study aims to investigate the epidemiological profile of patients and the diagnostic and therapeutic contribution of emergency laparoscopy at the Centre Hospitalier Auxerre (CHA) in France. It’s a year-long descriptive retrospective study conducted at the Auxerre Hospital. Out of 1130 laparoscopies, 245 were emergencies, i.e., 21.68% of laparoscopies. The mean age of our study population was 37 ± 22.78 years with patients ranging from 3 to 93-year-old. The sex ratio was 0.96. The main indications for emergency laparoscopies at CHA were acute appendicitis (44.9%) followed by exploratory laparoscopies (18.8%). Eight percent (8%) of the emergency laparoscopies were later converted to laparotomies, for the following reasons: difficult exposure, multiple adhesions, intestinal dilatation, hypercapnia. Regarding the surgical procedures, an appendectomy was performed in 37.1% of cases whereas peritoneal lavage and drainage following appendectomy were performed cavity in 18.4% of cases. We highlight a laparoscopic transdiaphragmatic pericardial fenestration performed to drain pericardial effusion due to cardiac tamponade, an uncommon procedure even in western practice. The mean duration of the procedure was 53 ± 32.52 minutes, ranging from 11 minutes and 214 minutes. The low postoperative morbidity of 6.53% in our study is one of the undeniable advantages of the laparoscopic approach. The other advantage of laparoscopy is the shortened hospital stay, even in the context of an abdominal emergency. Ample evidence of this is the average hospital stay of 5±5.4 days with 60.4% of patients spending less than 5 days in the hospital.
Keywords: aparoscopy-emergency-surgery.